Sport as a 'Tool' of Socialisation: Correlations between Civil Organisation Activity and Sporting Activity in the 15-18 Age Cohort - Takács, Bence; Kmetty, Zoltán (European Journal of Mental Health, 2014)
Correlations between Civil Organisation Activity and Sporting Activity in the 15–18 Age Cohort: Several studies pointed out the positive effects of social capital in the last 10 to 20 years. Nevertheless, only minor emphasis was put on the formation of social capital. Most authors implicitly presume an effect of socialisation in the background of the formation of social capital. This is also confirmed by studies, using data of panel research, which have demonstrated significant connections between the civil activity of young people and adults and their general level of trust. In our study we examine how membership in civil organisations – which we consider an important indicator of social capital – is influenced by sporting activity in the age range of 15–18. The two surveys examined (Ifjúságkutatás 2000, 2008) show that young people practising sports are more likely to participate in the work of civil organisations, moreover, sport proved to be a more important background variable in our models than the access to economic and cultural resources. Although this is also due to structural reasons, we are convinced that the most important factors for social capital are the participation in a community and the social net deriving from it. And juvenile sporting activity can serve as a good basis for this.